Time-lapse monitoring of fertilized human oocytes focused on the incidence of 0PN embryos in conventional in vitro fertilization cycles - Tatsuya Kobayashi (Nature Portfolio, 2021)
Abstract We aimed to investigate why the incidence of embryos derived from oocytes with no pronuclei (0PN) decreases using time-lapse monitoring (TLM) versus fixed-point assessment in conventional IVF cycles. We analyzed 514 embryos monitored with TLM 6–9 h after insemination and 144 embryos monitored using microscopic assessment 18–21 h after insemination. The primary endpoint of this study was the incidence of 0PN-derived embryos in short insemination followed by TLM. The secondary endpoint was the duration of insemination. As exploratory endpoints, we analyzed the blastulation rate and cryo-warmed blastocyst transfer outcome of embryos with early PN fading, whereby PN disappeared within < 20 h following the initiation of insemination. The incidence of 0PN-derived embryo reduced more significantly through TLM than through fixed-point observation. The microscopic assessment time was more significantly delayed in the 0PN-derived embryo than that in the 2PN-derived embryo. The embryo with early PN fading formed good-quality blastocysts, and their pregnancy outcomes were similar to those of other embryos. Most 0PN-derived embryos in the fixed-point assessment might have resulted from missed observation of PN appearance in the early-cleaved embryos. TLM or strict laboratory schedule management may reduce 0PN-derived embryos by reducing missed PN observations.